A Study on the Determinants of Organic Food Purchase Intention by Adult Consumers in Kolkata - Ghosh, Ankita; Lahiri, Isita (International Journal of Engineering and Management Research, 2025)
Purpose: The objective of the study is to evaluate how health, environment, awareness, affordability, taste and preferences influence Indian consumers’ intention to buy organic food. Methodology / Design: A descriptive research design was employed. Data were collected through structured questionnaires distributed among urban consumers in India. The responses were analysed using descriptive statistics and regression analysis to examine the influence of key factors on purchase intentions. Findings: Results indicate that health and taste considerations exert the strongest influence on buying decisions, while environmental and ethical concerns play a supporting role. Price and insufficient awareness remain major barriers to wider adoption. Limitations: The study is limited to urban respondents and a moderate sample size, which may reduce its general applicability across rural populations. Practical Implications: The findings provide guidance for marketers and policymakers to highlight health and taste benefits in promotional strategies, while simultaneously working to address cost and knowledge-related barriers. Value / Originality: This research enriches the limited body of work on organic consumer behaviour in India by offering empirical evidence from an emerging market, thereby contributing to a better understanding of how demographic and attitudinal factors shape organic food adoption.